A Conversation with Elisabeth Niklasson - Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2021)
Elisabeth Niklasson is lecturer at the School of Geosciences at the University of Aberdeen. She holds two master’s degrees in Cultural Heritage and Computational Archaeology from Gothenburg University, and a PhD in Archaeology from Stockholm University. She has long been interested in the ethical and political aspects of archaeological heritage, particularly relating to contemporary identity politics. A core part of her research has focused on European heritage policies, studying the influence of European Union (EU) funding schemes on archaeology. She has also reflected critically on the reception of aDNA in archaeology. In recent years, she has expanded her focus to analyse uses of the past by populist and extreme right movements in Europe, making vital contributions to our understanding of heritage in times of political polarization.